Non-technical skills for engineers in the 21st century: a basis for developing a guideline - Awang, Zubaidah; Zainal Abidin, Hafilah; Arshad, Md. Razib; Habil, Hadina (Universiti Teknologi Malaysia, 2006)
This study aims to determine the non-technical skills: functional and adaptive skills required by entry-level engineers in the manufacturing industry. These skills are divided into seven categories i.e. four functional skills categories(communication, creative thinking and problem solving, information management,leadership and organizational skills) and three adaptive skills categories (group effectiveness and teamwork, work-related dispositions and attitudes and personal traits and self-management). A total of 162 manufacturing firms participated in this study.Questionnaire was the main instrument used while interviews were used to provide an insight into non-technical skills required by entry-level engineers. This study found that non-technical skills are important for entry-level engineers in the manufacturing industry.Analysis of the functional skills found that the ability to follow procedure is the most important followed by the abilities to listen (listening), meet deadlines, manage time(time management) and work to schedule. As for adaptive skills, a majority of the respondents selected the following indicators: responsible, commitment, self-confidence,discipline, committed to the job and willingness to learn as the most valued traits. The findings of this study can be used as a basis for developing a guideline for non-technical skills to be included in the engineering curriculum. It is recommended that the current engineering curriculum at institutions of higher learning enhance both functional and adaptive non-technical skills. In addition, university-industry collaboration should be enhanced to address the skills gap of engineering graduates and the skills requirements of the manufacturing industry.